1999
DOI: 10.1073/pnas.96.20.11173
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Δ 5 -androstenediol-induced androgen receptor transactivation by selective steroids in human prostate cancer cells

Abstract: Our earlier report suggested that androst-5-ene-3␤,7␤-diol (⌬ 5 -androstenediol or Adiol) is a natural hormone with androgenic activity and that two potent antiandrogens, hydroxyf lutamide (Eulexin) and bicalutamide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Several 5 steroids derived from pregnenolone are active in humans and could activate the ancestral ER and PR. 5-Adiol (Kuiper et al, 1997) and 7-keto-DHEA and a 16-keto-derivative of 5-Adiol (Chang et al (1999) activate the mammalian ER. DHEA, pregnenolone and 7-hydroxy-pregnenolone are neurosteroids (Akawa et al, 1992, Compagnone andMellon, 1998;Baulieu and Robel, 1998).…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Several 5 steroids derived from pregnenolone are active in humans and could activate the ancestral ER and PR. 5-Adiol (Kuiper et al, 1997) and 7-keto-DHEA and a 16-keto-derivative of 5-Adiol (Chang et al (1999) activate the mammalian ER. DHEA, pregnenolone and 7-hydroxy-pregnenolone are neurosteroids (Akawa et al, 1992, Compagnone andMellon, 1998;Baulieu and Robel, 1998).…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…Moreover, these 7 -11 hydroxy-and 7 -hydroxy-steroids can be oxidized to 7-oxo-steroids [ Figure 4]. Support for the possibility that keto-5 steroids were ligands for the ancestral ER comes from the report by Chang et al (1999) that 100 nM 7-keto-DHEA and 16-keto derivative of 5-Adiol activated transcription mediated by the ER in MCF-7 breast cancer cells. These and other DHEA metabolites (e.g.…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…We showed that many DHEA metabolites, including ADEK, possess some estrogen activity, 15,16 suggesting that ADEK might cause not only castration effect but also some side effects, such as cardiovascular toxicity in vivo. Because of these unfavorable side effects, estrogens (e.g., DES) are rarely used as first-line hormonal treatment in spite of the evidence suggesting an additional benefit, a direct cytotoxic effect of estrogens through both estrogen receptor (ER)-dependent and ER-independent pathways in prostate cancer cells.…”
Section: Hormone Specificity Of Steroid Derivativesmentioning
confidence: 98%
“…We have synthesized a number of steroids and tested their antiandrogenic activity vs. Adiol and DHT. 15,16 The most effective was 3b-acetoxyandrosta-1,5-diene-17-one ethylene ketal (ADEK), which inhibits both DHT-and Adiol-induced AR transcription, PSA expression and growth in prostate cancer cells. Significantly, ADEK has marginal androgenic activity and a strong AR coactivator, ARA70, which has been shown to enhance agonist activity of clinically used antiandrogens, 17,18 fails to induce it.…”
mentioning
confidence: 99%
“…The human prostate cancer cell-line LNCaP expresses a mutant androgen receptor that allows it to respond to a wide variety of hormones, including the adrenal hormone AED (Miyamoto et al, 1998;Chang et al, 1999;Mizokami et al, 2004;He and Falany, 2007). Because of its potential role in sustaining prostate cancer cell growth after androgen deprivation therapy (ADT), we set out to determine whether a compound capable of inhibiting AEDstimulated LNCaP cell proliferation could be identified from a proprietary steroid library that was developed around the structure of AED.…”
Section: Discussionmentioning
confidence: 99%